The Effects of Mulligan Technique and Ultrasound on Pain and Functional Ability in Shoulder Impingement Condition at EMC Sentul Hospital - Widiani Retnaningsih; Yuli Peristiowati; Nurwijayanti Nurwijayanti (Eduvest - Journal of Universal Studies, 2024)
Shoulder impingement is a painful shoulder condition caused by injuries to the structures in the subacromial space. The research aims to analyze the effects of the Mulligan Technique and Ultrasound on pain and functional ability in shoulder impingement conditions at EMC Sentul Hospital. The research method used is a quasi-experimental design with pre and post-test control groups. Thirty participants were divided into two groups: an intervention group receiving the Mulligan Technique and Ultrasound (15 participants) and a control group receiving TENS and conventional exercise therapy (15 participants). Each participant underwent six sessions per week, twice a week. Before and after the treatment, each participant's pain level was measured using the Numeric Rating Scale (NRS), and functional ability was assessed using the Shoulder Pain and Disability Index (SPADI). The analysis of the data showed that both treatments in the two groups reduced pain and improved functional ability in shoulder impingement conditions. However, there was a significant difference in the group receiving the Mulligan Technique and Ultrasound, with an average pain reduction from 6.6 NRS to 1.3 NRS and an increase in functional ability from 62.6% to 11.85%. The group receiving TENS and conventional exercise therapy showed an average pain reduction from 3.6 NRS to 6.13 NRS and an increase in functional ability from 61.3% to 40.2%. In conclusion, the study suggests that the application of the Mulligan Technique and Ultrasound is more effective in reducing pain and improving functional abil-ity compared to TENS and conventional exercise therapy in shoulder impingement conditions.